The significance of a dementia diagnosis from the perspective of the family caregivers: a qualitative study - Inger Molvik; Grete Kjelvik; Geir Selbæk; Anne Marie Mork Rokstad (BMC Health Services Research)
Abstract Background With the anticipated increase in dementia prevalence over the coming decade, understanding the experience of receiving a dementia diagnosis for people living with cognitive impairment remains limited. This study aims to explore the implications of a family member with cognitive impairment receiving a dementia diagnosis or not from the perspective of their next of kin. Methods A qualitative descriptive design was applied using individual interviews for data collection. Participants were recruited based on the cognitive function level of their family members, which was compatible with dementia as assessed with the Montreal Cognitive Assessment Scale (MoCA). The sample consisted of eight participants, comprising family members of five individuals with confirmed dementia diagnoses and three undiagnosed. The analysis was performed using four steps of systematic text condensation to discern codes, categories, and the overarching theme. Results Three main categories were created: (1) Impact of observed cognitive decline, (2) Impact of diagnosis on service engagement, and (3) Support and follow-up for family caregivers. The findings show that next of kin who have received a dementia diagnosis for their family members are more proactive in seeking help and services, are better informed about available resources, and are more concerned about future challenges. On the other hand, next of kin to family members without a diagnosis are more inclined to handle the situation on their own, have less access to information and services, and generally express less concern about future problems. Conclusion The study reveals the benefits of receiving a timely dementia diagnosis in shaping more effective support systems and policies. This ensures that the next of kin and the person with cognitive impairment can navigate the complexities of dementia with greater confidence and preparedness, thereby enhancing their quality of life.